The active Hsc70/tau complex can be exploited to enhance tau turnover without damaging microtubule dynamics - Fontaine, Sarah N. (Hum Mol Genet, 2015)
The pathological accumulation of abnormally hyperphosphorylated and aggregated tau, a neuronal microtubule (MT)-associated protein that functions to maintain MT stability, is implicated in a number of hereditary and sporadic neurodegenerative diseases including frontotemporal dementia and Alzheimer's disease. Targeting tau for the treatment of these diseases is an area of intense interest and toward that end, modulation of cellular molecular chaperones is a potential therapeutic target. In particular, the constitutive Hsp70 isoform, Hsc70, seems highly interconnected with tau, preserving tau protein levels and synergizing with it to assemble MTs. But the relationship between tau and Hsc70, as well as the impact of this interaction in neurons and its therapeutic implications remain unknown. Using a human dominant negative Hsc70 that resembles isoform selective inhibition of this important chaperone, we found for the first time that Hsc70 activity is required to stimulate MT assembly in cells and brain. However, surprisingly, active Hsc70 also requires active tau to regulate MT assembly in vivo, suggesting that tau acts in some ways as a co-chaperone for Hsc70 to coordinate MT assembly. This was despite tau binding to Hsc70 as substrate, as determined biochemically. Moreover, we show that while chronic Hsc70 inhibition damaged MT dynamics, intermittent treatment with a small molecule Hsp70 inhibitor lowered tau in brain tissue without disrupting MT integrity. Thus, in tauopathies, where MT injury would be detrimental to neurons, the unique relationship of tau with the Hsc70 machinery can be exploited to deplete tau levels without damaging MT networks.